Effect of Sex, Level and Period of Feed Restriction During the Starter Stage on Productivity and Carcass Characteristics of Ross 308 Broiler Chickens in South Africa - Novele, D.J.; Ng`Ambi, J.W.; Norris, D.; Mbajiorgu, C.A. (International Journal of Poultry Science, 2008)
The effects of sex, level and period of feed restriction during the starter period on productivity and carcass characteristics of Ross 308 broiler chickens were evaluated. A 2 (male and female chickens) x 3 (feeding levels: Ad-libitum, 75% and 50% of ad libitum) x 3 (restriction periods of 5, 7 and 9 days) factorial arrangement in a complete randomized design was used. The effects of interactions were not included in the results because earlier analyses including all the interactions showed that they were not important. Level and period of feed restriction during the starter stage had an effect (P